Pedagogical Perspectives on Teaching Materials of Translation in English Language Teaching - Masitowarni Siregar (Script Journal: Journal of Linguistics and English Teaching, 2021)
Background: This research paper attempts to analyze the vocational English instructors’ view point on the cultivation of teaching material of Pedagogical Translation in the Subject of Translation in English Language Teaching (ELT). Methodology: The qualitative design was used to collect the data. Utilizing the questionnaire with Likert Scale, the quantitative data were gained from 30 vocational English teachers in Sumatera Utara Province. Findings: Data obtained revealed that 52.45 % of respondents agreed with the teaching material, and 43.10 % strongly agreed with those. Only 4.45 % of respondents strongly disagreed with those topics. Data analysis showed that the 58 elements in the Subject of Translation in ELT have covered the teaching materials in Vocational school. Conclusion: It was concluded, within nine areas questioned to the vocational English teachers, most of them (92%) agree with the statements. Furthermore, all the respondents 100% are in the opinion that there should be English for vocational school materials included within the translation materials studied in the Subject on Translation in ELT.